Influence radius of pressure relief of energy-accumulating blasting and water injection in the heading face of the liangbei coal mine - Zhenfeng Wang; Zhenfeng Wang; Yu Wang; Feng Wang (Frontiers in Earth Science, 2023)
This study aims to reasonably determine the influence radius of pressure relief of energy-accumulating blasting and water injection in the Liangbei Coal Mine and effectively eliminate local stress concentration and coal seam outburst risk. The change in gas parameters in each test hole before and after energy-accumulating blasting and water injection is determined through ANSYS/LSDYNA numerical simulation, theoretical analysis and calculation, and the application of the gas parameter method in the 32051 heading face of the Liangbei Coal Mine. The influence radius of pressure relief technology of energy-accumulating blasting and water injection in the Liangbei Coal Mine in the direction of energy-accumulating trough is studied, which provides reliable data for the layout parameters of energy-accumulating blasting and water injection hole in the working face of the Liangbei Coal Mine. The experimental results are as follows: 1) The simulation via ANSYS/LSDYNA shows that a blasting cavity is formed by an explosive shock wave in the borehole. The diameter of the blasting cavity in the energy-accumulating direction is 42 cm, which is 10 times the diameter of the energy-accumulating blasting and water injection hole. The diameter of the blasting cavity in the non-energy-accumulating direction is 14 cm, which is 3.3 times the diameter of the energy-accumulating blasting and water injection hole. The stress in the energy-accumulating direction is 2.9 times larger than that in the non-energy-accumulating direction. The crack length in the energy-accumulating direction is 294 cm, and the crack length in the non-energy-accumulating direction is 80 cm. 2) Theoretical analysis and calculation present that the crushing area of shaped charge blasting is 39 cm, the fracture area is 267 cm, and the vibration area is 159 cm. 3) Comparison of the change in gas parameters of each test hole in the field experiment before and after energy-accumulating blasting and water injection indicates that the influence radius of pressure relief in the direction of energy-accumulating trough is 300 cm. 4) The layout of energy-accumulating blasting and water injection in the working face of the Liangbei Coal Mine with 550 cm borehole spacing demonstrates that the verification index of gas drilling decreases, the analytical values (Δh2) decrease from 120–140 Pa to 100–120 Pa, the drilling cutting weight (S) decreases from 3.2 to 4.6 kg/m to 3.0–3.8 kg/m, and stress is released and transferred to deep coal. This study has guiding significance for outburst elimination by local arrangement of energy-gathering blasting and water injection borehole in the working face of the Liangbei Coal Mine.